Generalizations of Steffensen’s Inequality by Lidstone’s Polynomials - Pečarić, J. E.; Perušić, A.; Smoljak, K. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We obtain generalizations of Steffensen’s inequality by using Lidstone’s polynomials. Furthermore, the functionals associated with the obtained generalizations are used to generate n-exponentially and exponentially convex functions, as well as the new Stolarsky-type means.